Prevalence of Subclinical Carotid Atherosclerosis and Vitamin D Deficiency in Egyptian Ankylosing Spondylitis Patients - Dina Salem FOTOH; Dena Mamdouh SERAG; Ismail Tawfeek BADR; Dalia Salah SAIF (Archives of Rheumatology, 2020)
Objectives: This study aims to investigate the relationship between subclinical carotid atherosclerosis and vitamin D deficiency in Egyptian ankylosing spondylitis (AS) patients and their impact on disease activity. Patients and methods: This cross-sectional study included 40 AS patients (36 males, 4 females; mean age 45.9±8.4 years; range 33 to 55 years) diagnosed according to the 1984 modified New York criteria with equal number of healthy controls (26 males, 14 females; mean age 48.4±7.8 years; range 31 to 55 years). Patients’ histories were taken and clinical examinations were performed. Disease activity was assessed with Bath AS metrology index (BASMI), Bath AS disease activity index (BASDAI), and Bath AS functional index (BASFI) scores. Laboratory evaluation included lipid profile and 25-hydroxyvitamin D [25(OH)D] was determined by enzyme-linked immunosorbent assay. Bilateral carotid intima-media thickness (CIMT) was measured by a high-resolution ultrasound with linear 7-12 MHz transducer. Average of CIMT of right and left common carotid arteries was used. Results: Statistically significant differences were found between patients and controls in terms of CIMT (p<0.001), 25(OH)D3 (p<0.001) and triglycerides (p=0.02). A significant positive correlation was present between CIMT and disease duration (r=0.74), disease activity scores [BASFI (r=0.60), BASMI (r=0.49), BASDAI (r=0.65)] and lipid profile except for high-density lipoprotein (HDL) that had a negative correlation (r=-0.52). A significant negative correlation was present between 25(OH)D3 levels and CIMT (r=-0.38) and lipid profile except for HDL having a positive correlation (r=0.40). Conclusion: Prevalence of subclinical carotid atherosclerosis in AS patients compared to the healthy population was associated with high disease activity and functional limitations. In AS patients, 25(OH)D3 deficiency is a risk factor for accelerated atherosclerosis.